The Impact of Corporate Governance Implementation and Debt Financing on Manufacturer’s Firm Performance: Evidence from Emerging Country - Soesetio, Yuli; Adiningsih, Gwen Sukma; Rudiningtyas, Dyah Arini (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This study aims to examine the influence of corporate governance and debt financing practices on the dynamics of firm performance in the manufacturing sector listed on the Indonesia Stock Exchange (IDX). Methodology/approach – This quantitative research paper uses secondary data from the financial statements of manufacturing sector firm for 11 years, between 2009 and 2019. The number of samples that met the established criteria was 190 firm, which were further analyzed using panel regression analysis. Findings – This study concludes that the application of corporate governance in the manufacturing sector, has both a consistently positive effect on ROA and ROE. Meanwhile, debt financing is based on the analysis of total debt ratio, long debt ratio, and short debt ratio in accordance with profitability and trade off theory. Novelty/value – This study aims to provide a more general and robust conclusion regarding the effect of implementing corporate governance mechanisms and debt financing decisions on firm performance in emerging country, especially in the manufacturing sector by using periods, samples, variables and analyzing debt ratios with various time periods.